Investigation of feeding and nutritional problems related to long-term enteral nutrition support among children with disabilities: a pilot study - Zaher, Sara; Aldhowayan, Hadeel; Almalki, Asmaa; Alsaedi, Riman; Almghamsi, Ruba; Aljazaeri, Lujain; Mumena, Walaa Abdullah (Frontiers in Nutrition, 2025)
BackgroundEnteral Nutrition (EN) is considered a standard intervention for patients with disabilities who cannot meet their nutritional requirements orally and are at risk for malnutrition secondary to eating difficulties. The current study examined common feeding and nutritional problems related to prolonged EN among disabled children.MethodsA cross-sectional, pilot study was conducted in Saudi Arabia between December 2023 and March 2024. Caregivers of children with disabilities were invited to complete an online questionnaire that gathered demographic data and explored feeding difficulties and challenges related to enteral nutrition.ResultsA total of 41 caregivers completed the survey regarding their children. The median age (IQR) of disabled children was 3.2 (1.7–6.6) years. The most frequently reported feeding and nutritional problems in this cohort were constipation [median = 3.0, IQR: 2.0–4.0], weight loss [median = 3.0, IQR: 1.0–4.0], and gastroesophageal reflux [median = 2.0, IQR: 1.0–3.0].The regression analysis showed a statistical association between the indication for nutrition support and the subsequent detected feeding/nutritional problem, p-value<0.05. It also showed that the primary diagnosis (r = 0.459, p-value = 0.003) and health status (r = 0.458, p-value = 0.003) were statistically significant predictors of the frequency of reported feeding and nutritional problems among this children group. Additionally, the challenges experienced by the caregivers were statistically related to the type of EN provided (r = 0.491, p-value = 0.001).ConclusionThe study provided insight into the typical feeding and nutritional problems associated with long-term EN among children with disabilities. Identifying these issues can support early diagnosis and the implementation of appropriate nutritional interventions, ultimately helping to optimize growth and improve quality of life for these children.